Outcomes after resumption of immune checkpoint inhibitor therapy after high‐grade immune‐mediated hepatitis - Michael Li; Jordan Sack; Osama E. Rahma; F. Stephen Hodi; Stephen D. Zucker; Shilpa Grover (2020)
Background In the current study, the authors assessed the risks and outcomes of immune checkpoint inhibitor (ICI) rechallenge in patients with resolved grade 3 to 4 ICI hepatitis because current guidelines recommend permanent ICI discontinuation in these patients. Methods The authors performed a retrospective cohort study from 2010 through 2019 of patients with melanoma who were treated with ≥1 ICIs and who recovered from grade 3 to 4 ICI hepatitis. The primary outcome was hepatitis recurrence and the secondary outcome was the development of any immune‐related adverse event (irAE) requiring the discontinuation of ICI rechallenge. Best overall response and time to all‐cause death were compared between the patients who did and those who did not undergo ICI rechallenge. Grading was performed using the National Cancer Institute Common Terminology Criteria for Adverse Events (version 5.0). Results Of the 102 patients with melanoma who developed high‐grade ICI hepatitis, 31 underwent ICI rechallenge. Although 15 of 31 patients (48%) developed an irAE of any grade, only 6 patients (19%) required ICI discontinuation due to irAE severity (4 of 29 patients [14%] rechallenged with anti–PD‐1 or anti‐PD‐L1 and 2 of 2 patients [100%] rechallenged with ipilimumab). Recurrent hepatitis accounted for 4 of these 6 cases. Rechallenged patients who did not require ICI discontinuation were found to be significantly less likely to receive ipilimumab rather than anti–PD‐1 or anti‐PD‐L1 monotherapy (0% vs 33%; relative risk (RR), 0.1 [95% CI, 0.1‐0.3; P = .032]) and significantly less likely to be rechallenged with their original ICI (8% vs 50%; RR, 0.2 [95% CI, 0.1‐0.7; P = .038]). There was no difference noted with regard to best overall response or time to death between rechallenged and non‐rechallenged patients. Conclusions ICI therapy can be resumed in patients with melanoma who have recovered from grade 3 to 4 ICI hepatitis with a modest risk of serious irAEs. It remains unclear whether ICI retreatment improves clinical outcomes.